Notes on a suicide a critical discourse analysis of the newspaper coverage of the Mariannet Amper suicide - Serafica, Gladys G. (College of Mass Communication, University of the Philippines Diliman, 2014)
"Much has been written about the effect of media reporting in public opinion about suicide, however, there is a dearth of studies that look at the discursive reality constructed by the newspapers regarding this phenomenon. Using the Critical Discourse Analysis approach, this study sought to determine the news discourse constructed by leading newspapers vis-a-vis the socio-cultural context and media culture in their coverage of Mariannet Amper, the 12-year-old-girl from Davao who committed suicide on November 2007. Consistent with the aim of CDA to pursue emancipatory goals, the study exposed the ethical lapses and determined what within the discourse allowed for the ethical lapses committed by the newspapers, in the hope that by making them explicit, such unethical practices can be contested, and in the long run, changed. The relation power specifically, how certain social structures influence the discourse and maintain their dominance through the use of media was also explored in this study. Findings of the study showed that socio-cultural factors, the newspapers' political orientation, and their social relationship with other social structures shaped the conditions and constraints of the newspaper coverage of the Mariannet Amper suicide."